Cellulolytic Enzymes Production via Solid-State Fermentation: Effect of Pretreatment Methods on Physicochemical Characteristics of Substrate - Brijwani, Khushal (SAGE-Hindawi Access to Research, 2011)
We investigated the effect of pretreatment on the physicochemical characteristics—crystallinity, bed porosity, and volumetric specific surface of soybean hulls and production of cellulolytic enzymes in solid-state fermentation of Trichoderma reesei and Aspergillus oryzae cultures. Mild acid and alkali and steam pretreatments significantly increased crystallinity and bed porosity without significant change inholocellulosic composition of substrate. Crystalline and porous steam-pretreated soybean hulls inoculated with T. reesei culture had 4 filter paper units (FPU)/g-ds, 0.6 IU/g-ds β-glucosidase, and 45 IU/g-ds endocellulase, whereas untreated hulls had 0.75 FPU/g-ds, 0.06 IU/g-ds β-glucosidase, and 7.29 IU/g-ds endocellulase enzyme activities. In A. oryzae steam-pretreated soybean hulls had 47.10 IU/g-ds endocellulase compared to 30.82 IU/g-ds in untreated soybean hulls. Generalized linear statistical model fitted to enzyme activity data showed that effects of physicochemical characteristics on enzymes production were both culture and enzyme specific. The paper shows a correlation between substrate physicochemical properties and enzyme production.